Indirect Corrective Feedback on Writing Accuracy of Students Across Different Level of Grammatical Sensitivity - Zuraida Zuraida; Lutin Nur R.R (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
People tend to communicate their ideas, opinion, and views through writing. However, in English language learning context in Indonesia, writing is usually thought as the most challenging skill to be mastered. As language facilitator, teacher has to be able to provide the students with teaching strategy that can assist them to master writing skill. A quasi-factorial design was aimed at investigating the effect of indirect corrective feedback on students’ writing accuracy viewed from the different level of students’ grammatical sensitivity. There were control and experimental group. The experimental group was exposed to the use of indirect corrective feedback, while control group was exposed to the use of direct corrective feedback. Independent T-Test and Two-way ANOVA were used to test the hypotheses. The study revealed that there was significance difference on writing accuracy between the experimental and control group. Students with high level of grammatical sensitivity got higher mean score than the lower students. There was no interaction between indirect corrective feedback on writing accuracy and students’ level of grammatical sensitivity. It is recommended to the English teacher to use indirect corrective feedback to assist the students’ learning on writing.